Analisis Penyebab Terjadinya Pembengkakan Biaya (Studi Kasus: Pada Proyek-Proyek Di Kota Pekanbaru) - Wan Bunda Theresia; Rian Tri Komara Iriana; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The construction project is an activity which has a goal to be achieved. In the construction process, the cost is the major consideration because it commonly involves a large amount of investment and is vulnerable to the risk of failure. The purpose of this research was to determine the rate of validation, and to analyze the most dominant factor causing the overrun of construction costs (case study on Municipal Projects in Pekanbaru). The collected data were analyzed by using validation and reliability test, factor analysis, classic assumption test, and multiple linier regression. The data processing was done by using SPSS software (Statistical Product and Service Solution) version 23. As a result, it is obtained that the most dominant factor which has triggered the overrun cost consisted of: planning and construction department i.e. handling too many projects at the same time with the percentage of 83,9%, part of the cost estimate that does not take into account the unexpected cost with a 92.0% percentage on the road, part of the cost estimate that does not take into account the unexpected cost with a percentage of 90.1% on the bridge.Keywords : construction, cost, overrun cost, dominant factor.